2011
DOI: 10.3390/ijms12129514
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds in Honey: A Review on Their Involvement in Aroma, Botanical Origin Determination and Potential Biomedical Activities

Abstract: Volatile organic compounds (VOCs) in honey are obtained from diverse biosynthetic pathways and extracted by using various methods associated with varying degrees of selectivity and effectiveness. These compounds are grouped into chemical categories such as aldehyde, ketone, acid, alcohol, hydrocarbon, norisoprenoids, terpenes and benzene compounds and their derivatives, furan and pyran derivatives. They represent a fingerprint of a specific honey and therefore could be used to differentiate between monofloral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
187
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(202 citation statements)
references
References 67 publications
(131 reference statements)
3
187
0
3
Order By: Relevance
“…The studies shown that topical pure honey reduces oral mucositis as dramatical [37,38]. The antioxidant, antiproliferative, antimicrobial effects of 3 to 20g of honey demonstrated in multiple studies [38][39][40][41][42][43]. In Islamic medicine and Iran, the combination of NS with honey is used for alleviating gastrointestinal symptoms like abdominal pain, bloating and diarrhea [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The studies shown that topical pure honey reduces oral mucositis as dramatical [37,38]. The antioxidant, antiproliferative, antimicrobial effects of 3 to 20g of honey demonstrated in multiple studies [38][39][40][41][42][43]. In Islamic medicine and Iran, the combination of NS with honey is used for alleviating gastrointestinal symptoms like abdominal pain, bloating and diarrhea [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…VOCs in honey originate from different biosynthetic pathways and contribute to the development of honey distinguishable aroma, which is greatly affected by botanical and geographical origin [1,2]. Despite their presence in low proportions, VOCs could contribute to biomedical activity of honey due to their natural radical scavenging activity potential [1].…”
mentioning
confidence: 99%
“…On the other hand, there is a great tendency for simple, fast, non-expensive, and eco-friendly methodologies to be applied on the quality control of agricultural products [1].…”
mentioning
confidence: 99%
See 2 more Smart Citations